Study on Lateral Bearing Characteristics of Geotextile Bag Retaining Wall of Two-Stage Slope - GUAN Xiaodi; QIN Zexuan (Renmin Zhujiang)
Under the background of the rapid development of high-speed traffic and the popularization of low-carbon life,the ecological slope protection technology with geotextile bags has attracted wide attention.To investigate the lateral bearing characteristics of two-stage slopes supported by the geotextile bag retaining wall,we conduct lateral non-uniform loading tests of a two-stage slope under the conditions of inclined support,L-shaped support,and reverse-slope L-shaped support.The analysis of the tests indicates that the horizontal displacement of the two-stage slope is greater than that of a one-stage slope,and the earth pressure increases with the increase in wall height.Through the comparison of test results,it is found that with the slope with inclined support as a reference,the arch height of the slope top is increased by 22.2% and 59.3% in the case of L-shaped support and reserve-slope L-shaped support,respectively,and the earth pressure at the two-stage slope toe is increased by 11.1% and 19.2%,with that at the one-stage slope toe increased by 24.7% and 35.8%,respectively.The failure mode analysis shows that the failure of the two-stage slope occurs before that of the one-stage slope,which is a sliding failure,and the sliding surface is a circular arc.Finally,the correctness of the model test results is verified by ABAQUS.